Strategi Dinas Sosial dalam Penanganan Anak Punk di Kota Cilegon - Iman, Muhammad; Handayani, Riny; Maisaroh, Ima (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
The punk phenomenon in Indonesia has developed since the 1990s and has become part of the dynamics of urban public space subcultures. In its development, punk children are often confronted with negative stigma as part of street children and social welfare problems, which requires policy responses that are not merely repressive but also rehabilitative. This study aims to analyze the strategy of the Social Service (Dinas Sosial) in handling punk children. The research employs a descriptive qualitative approach. Data were collected through  observation, in-depth interviews, and documentation studies. Data analysis was conducted using the Miles and Huberman model, with data validity ensured through triangulation and member checking. The analytical framework refers to Mulgan’s public sector strategy theory, which includes the dimensions of purpose, environment, direction, action, and learning. The findings indicate that the Social Service has established formal objectives and implemented outreach and social rehabilitation programs, supported by coordination with relevant agencies. However, the strategy has not been optimally implemented due to limited continuity of post-intervention assistance, underutilization of shelter facilities, and weak evaluation and policy learning mechanisms in responding to the high mobility characteristics of punk children. This study recommends strengthening cross-sector collaboration, enhancing continuous assistance, optimizing social rehabilitation facilities, and reinforcing monitoring and policy learning to improve the effectiveness and sustainability of punk children handling.